2018
DOI: 10.1016/j.bbmt.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Shortened-Duration Tacrolimus after Nonmyeloablative, HLA-Haploidentical Bone Marrow Transplantation

Abstract: With post-transplantation cyclophosphamide (PTCy) as graft-versus-host disease (GVHD) prophylaxis, nonmyeloablative HLA-haploidentical (NMA haplo) and HLA-matched blood or marrow transplantation (BMT) have comparable outcomes. Early discontinuation of immunosuppression may reduce the risk of relapse and improve immune reconstitution, but may increase the risk of GVHD. We conducted a prospective trial of NMA haplo BMT for patients with hematologic malignancies (median age, 61 years), evaluating the safety of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This supports the avoidance of systemic immunosuppression to treat skin-only grade II aGVHD, when possible, because most cases can be watched expectantly without necessitating the reinitiation of immunosuppression; such an approach could limit side effects, infectious risk, and maintain the graft-versus-tumor effects of GVHD. We have previously shown that PTCy minimizes the global immunosuppressive burden experienced by patients undergoing HLA-matched BMT [15], and this work emphasizes the importance of exploring the further minimization of pharmacologic agents post-transplant in other platforms such as reported recently by our group in haplo BMT with PTCy [39]. Although this and other recent studies [9,15,39,40] suggest that potent anti-tumor immune responses are maintained with PTCy, fully deciphering these interactions requires further mechanistic studies.…”
Section: Discussionmentioning
confidence: 85%
“…This supports the avoidance of systemic immunosuppression to treat skin-only grade II aGVHD, when possible, because most cases can be watched expectantly without necessitating the reinitiation of immunosuppression; such an approach could limit side effects, infectious risk, and maintain the graft-versus-tumor effects of GVHD. We have previously shown that PTCy minimizes the global immunosuppressive burden experienced by patients undergoing HLA-matched BMT [15], and this work emphasizes the importance of exploring the further minimization of pharmacologic agents post-transplant in other platforms such as reported recently by our group in haplo BMT with PTCy [39]. Although this and other recent studies [9,15,39,40] suggest that potent anti-tumor immune responses are maintained with PTCy, fully deciphering these interactions requires further mechanistic studies.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, it is of note that GFRS in our cohort compared favorably to the one in AML patients treated with ATG instead of PTCY for GvHD prophylaxis in TCR haplo-HSCT, 45 Recently, Kasamon et al reported on the safety of early cessation of postgrafting immunosuppression in the TCR haplo-setting using PTCY for GvHD prophylaxis. If using this safe platform, 49 we might get in the favorable position to apply pDLI earlier in the course after haplo-HSCT. However, their experience is not so easy to translate into ours in patients with high-risk, r/r AML/MDS: BM was the only graft source used, whereas we used PBSCs in~50% of the cases which is associated with a higher GvHD incidence per se in TCR haplo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates for 1-, 2-, and 3-year DFS were 49% (95% CI: 46-52), 46% (95% CI: [43][44][45][46][47][48][49], and 40% (95% CI: 37-43), respectively. Out of six patients who did not develop aGvHD, five died due to early relapse within the first year (1-year DFS: 70% vs 0%; P < .0001) (Supporting Information, Table 3).…”
Section: Survivalmentioning
confidence: 98%
“…As such, for patients with MRD in whom additional pretransplantation therapy is not pursued, we prefer allografting with PBSCTs and/or for early cessation of immunosuppression, which was associated with less relapse in a small study of BM allografts. 62 In addition, a clinical trial using maintenance therapies (eg, enasidenib, ivosidenib, idelalisib, gilteritinib, blinatumomab, venetoclax, and APR-246) or prophylactic posttransplantation immunotherapy (donor lymphocyte or natural killer cell infusion) to prevent relapse should be considered in these high-risk patients.…”
Section: Do Mrd and Active Disease Matter?mentioning
confidence: 99%
“…In a recent publication, after haplo-BM allografting with PTCy, tacrolimus could be stopped as early as day 60 after transplantation. 62 Clinical trials are ongoing in patients who have undergone allografting using haplo-PBSCT with PTCy to examine whether immunosuppression can safely be discontinued on day 90.…”
Section: Questions Continuedmentioning
confidence: 99%